Catalog of the New World Biting Midges North of Mexico (Diptera: Ceratopogonidae) - Borkent, Art; Grogan, Jr., William L. (Zootaxa, 2009)
This catalog of the biting midges (Diptera: Ceratopogonidae) of the New World north of Mexico includes 603 species and 39 genera. The full citation, province or state of the type locality and distribution by province and/or state of each species is given. The most recent revision for each genus, subgenus and species group is cited.